1999
DOI: 10.1002/pdi.1960160605
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of prevalence of asymptomatic peripheral arterial occlusive disease in patients with diabetes attending a hospital clinic

Abstract: In a pilot studyJ we have estimated the crude prevalence of asymptomatic peripheral arterial occlusive disease (PAOD) in diabetic patients attending a hospital clinic, using the sensitive Doppler ultrasound measurement of systolic ankle brachial pressure index (ABPI). This was compared with the available clinical methods of PAOD detection, ie peripheral pulse palpation. We have also investigated whether the measurement of toe systolic pressure (TSP) improved the detection rate of PAODamongst those who hada nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…However, several recent developments suggest that this may be an opportune time to reexamine traditional assumptions regarding methods used to diagnose and manage PAD. These developments include (1) data from recent community surveys of PAD prevalence, treatment, and outcomes, which have shed new light on the magnitude of the burden of PAD and its undertreatment [2][3][4] ; (2) a large body of epidemiologic evidence supporting the efficacy of the anklebrachial index (ABI [also known as the ankle-brachial pulse index or the ankle/arm index]) as an effective diagnostic and risk-assessment tool [5][6][7][8] ; (3) increasing awareness of the costeffective benefit associated with the management of cardiovascular risk 9 ; and (4) clinical study results showing that substantial risk reduction can be achieved with pharmacologic intervention in PAD. [10][11][12] This call-to-action document is an initiative of the Prevention of Atherothrombotic Disease Network, an international, independent group comprising specialists in the fields of vascular medicine, neurology, diabetology, nephrology, cardiology, and primary care.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent developments suggest that this may be an opportune time to reexamine traditional assumptions regarding methods used to diagnose and manage PAD. These developments include (1) data from recent community surveys of PAD prevalence, treatment, and outcomes, which have shed new light on the magnitude of the burden of PAD and its undertreatment [2][3][4] ; (2) a large body of epidemiologic evidence supporting the efficacy of the anklebrachial index (ABI [also known as the ankle-brachial pulse index or the ankle/arm index]) as an effective diagnostic and risk-assessment tool [5][6][7][8] ; (3) increasing awareness of the costeffective benefit associated with the management of cardiovascular risk 9 ; and (4) clinical study results showing that substantial risk reduction can be achieved with pharmacologic intervention in PAD. [10][11][12] This call-to-action document is an initiative of the Prevention of Atherothrombotic Disease Network, an international, independent group comprising specialists in the fields of vascular medicine, neurology, diabetology, nephrology, cardiology, and primary care.…”
Section: Introductionmentioning
confidence: 99%
“…17 An Indian study done by Bembi V et al reported 24% prevalence of PAD in diabetics. 18 Using ABI to identify PAD, the prevalence of PAD in people with DM over 40 years of age has been estimated to be 20% as reported by Elhadd TA et al 19 This prevalence increases to 29% in patients with DM over 50 years of age. The severity and duration of DM are important predictors of both the incidence and the extent of PAD, as observed in United Kingdom Prospective Diabetes Study, where each 1% increase in glycosylated hemoglobin was correlated with a 28% increase in incidence of PAD, and higher rates of death, microvascular complications and major amputation as reported by Selvin E et al and Jude EB et al 20,21 Dick F et al reported the prevalence of concomitant PAD and DM is especially high in those patients who have critical lower limb ischemia, with more than 50% of patients with critical limb ischemia (CLI) also having DM.…”
Section: Discussionmentioning
confidence: 85%
“…24 The POPADAD study assessed 8,000 diabetic people aged ≥40 years and found a PAOD prevalence of 20.1%. 25 In our setting, a multicenter study into the prevalence of PAOD among the general population (n=1,170) of 72 urban centers in Brazil found a prevalence of just 10.5%. It is worth noting that the age range was lower (≥18 years) and the sample was more representative of the Brazilian population because it was not comprised of genetically homogenous subjects nor of people at high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%